STUDI KUALITAS PELAYANAN PADA SOSIAL MEDIA INSTAGRAM NINJA XPRESS TERHADAP PENINGKATAN CITRA PERUSAHAAN - Uljanatunnisa, Aditya Krisna Putri, Yani Hendrayani, (MEDIALOG: Jurnal Ilmu Komunikasi, 2020)
This study discusses quality of service study in social media instagram of Ninja Xpress against improving the corporate image. The purpose of this research is to know the magnitude of the influence quality of service against improving corporate image on delivery service of Ninja Xpress. The model used in this study is a model of the formation of images. The method used is quantitative. This research using survey method by using a questionnaire. The population in this research is a followes of Ninja Xpress?s Instagram, for the sample Yamane formula using which then obtained as many as 99 of respondents. Sample withdrawal techniques used in this research is purposive sampling technique. The research results showed that test results correlation variable X (quality of service) against the variable Y (the corporate image) of 0,821. Based on the results of the calculation of the coefficient of determination of the obtained results the presence of the influence of variables X against Y variables of 67,4% it means the results of the influences is significant between variables X against Y variables. T test results in apat t calculate > t table i.e. t calculate 14,184 > 1,661 table t, then it can be inferred H0 is rejected and the Ha are received. The conclusion from research that Instagram of Ninja Xpress account must always be active in interacting with their customers and making the latest innovations in Instagram content uploads.